1969
DOI: 10.1063/1.1671178
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Shielding of 19F in XeF2

Abstract: The rigid-lattice second moment of the 19F nuclear magnetic resonance of XeF2 has been measured as a function of the external magnetic field. The experimental shielding anisotropy | Δσ | = 105 ± 10 × 10−6 does not agree closely with a value of σ⊥ − σ‖ = − 506 × 10−6 previously calculated using a localized orbital model. The field-independent rigid-lattice second moment is ∼ 0.4 G2 larger than that calculated from crystallographic data, probably because of large amplitude vibrations in XeF2. The temperature dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1970
1970
2004
2004

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Inclusion of the 1 J( 129 Xe-19 F) coupling constant (À5550 Hz) as well as the heteronuclear dipolar coupling between 19 F and 129 Xe in XeF 2 (3940 Hz) in the simulations reproduced the skewing observed for the 129 Xe satellites. The 19 F SA determined in the present study is in good agreement with the value found previously based on second-moment measurements at three different field strengths [6].…”
Section: F Nmr Spectroscopysupporting
confidence: 87%
See 2 more Smart Citations
“…Inclusion of the 1 J( 129 Xe-19 F) coupling constant (À5550 Hz) as well as the heteronuclear dipolar coupling between 19 F and 129 Xe in XeF 2 (3940 Hz) in the simulations reproduced the skewing observed for the 129 Xe satellites. The 19 F SA determined in the present study is in good agreement with the value found previously based on second-moment measurements at three different field strengths [6].…”
Section: F Nmr Spectroscopysupporting
confidence: 87%
“…The spin-1/2 nuclides, 129 Xe and 19 F, have found extensive use in the characterization of xenon compounds, nearly all of which are derived from the parent binary fluorides, XeF 2 , XeF 4 , and XeF 6 . Both nuclides have high receptivities, with 19 F having a receptivity relative to that of 1 H of 0.834, and 129 Xe (natural abundance, 26.44%) a receptivity 32.4 times that of natural abundance 13 C. The large number of experimental NMR parameters for xenon compounds in solution [1] is in marked contrast with the relative paucity of NMR data that have been reported for xenon compounds in the solid state [2][3][4][5][6]. The gas-phase NMR spectroscopy of xenon compounds has been neglected with no NMR spectroscopic measurements having been reported.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…29 M2=M2(field independent) + (4/45)[( uz-ux )2 +(uy-u z )(uy-u x )]H02. (1) The equation is completely general and is not changed by a permutation of x, y, and z, which results in U x , U y , and U z being indistinguishable. In the case of axial symmetry, Ux=Uy and Eq.…”
Section: Discussionmentioning
confidence: 99%
“…3 for the rigid lattice and above the motional transition relate to Eqs. (1) and (3), respectively. In addition, the total absolute shielding may be expressed as (4) From the shape of the higher temperature resonance in Fig.…”
Section: Discussionmentioning
confidence: 99%